Exploring the Connections between Spirituality and Morality: Phenomenology Study on Tijaniyyah Sufi Order’s Congregation in Jatibarang Brebes - Saepudin Saepudin (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2017)
This article aims at revealing the connections between aspects of spirituality and morality which are able to present happiness and tranquility. One of them is through the approach implicitly implemented in aurad ritual, which is performed by Tijaniyyah sufi order’s congregation at Jatibarang Brebes. It has proven to breaking down the value of the community from bad to good. This phenomenological study, investigates the emergence of the congregation was caused over the human behavior decadence in the midst of modern society. System carried out by Tijaniyyah in renewing the morality of society following the manhaj of prophet Muhammad i.e. through akhlakiyah (ethic) approach. To prove the truth of this Tijaniyyah mission against the moral improvement of society, congregations do a ritual that is lazimah dan wadifah which aims at forming behavior change, especially on its followers. The results of this study show that Tijaniyyah’s congregations at Jatibarang Brebes assert the existence of a sense of serenity in their own life. In addition, they always istiqamah (consistent and commitment) in dealing with any mundane problem.